Ambient Air Pollution Is Associated With HDL (High-Density Lipoprotein) Dysfunction in Healthy Adults. Issue 3 (March 2019) - Li, Jianping; Zhou, Changping; Xu, Hongbing; Brook, Robert D.; Liu, Shengcong; Yi, Tieci; Wang, Yang; Feng, Baihuan; Zhao, Mingming; Wang, Xu; Zhao, Qian; Chen, Jie; et al.
Abstract : Objective—: We aimed to assess whether exposure to higher levels of ambient air pollution impairs HDL (high-density lipoprotein) function and to elucidate the underlying biological mechanisms potentially involved. Approach and Results—: In the Beijing AIRCHD study (Air Pollution and Cardiovascular Dysfunction in Healthy Adults), 73 healthy adults (23.3±5.4 years) were followed-up with 4 repeated study visits in 2014 to 2016. During each visit, ambient air pollution concentrations, HDL function metrics, and parameters of inflammation and oxidative stress were measured. Average daily concentrations of ambient particulate matter in diameter <2.5 μm were 62.9 µg/m 3 (8.1–331.0 µg/m 3 ). We observed significant decreases in HDL cholesterol efflux capacity of 2.3% (95% CI, −4.3 to −0.3) to 5.0% (95% CI, −7.6 to −2.4) associated with interquartile range increases in moving average concentrations of particulate matter in diameter <2.5 μm and traffic-related air pollutants (black carbon, nitrogen dioxide, and carbon monoxide) during the 1 to 7 days before each participant's clinic visit. Higher ambient air pollutant levels were also associated with significant reductions in circulating HDL cholesterol and apoA-I (apolipoprotein A-I), as well as elevations in HDL oxidation index, oxidized LDL (low-density lipoprotein), malondialdehyde, and high-sensitivity C-reactive protein. Conclusions—: Higher ambient air pollution concentrations were associated with impairments in HDL functionality, potentially because of systemic inflammation and oxidative stress. These novel findings further our understanding of the mechanisms whereby air pollutants promote cardiometabolic disorders. Abstract : Supplemental Digital Content is available in the text.